2003
DOI: 10.1210/jc.2002-021603
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Supplementation Improves Endothelial Function and Insulin Sensitivity in Men

Abstract: The dehydroepiandrosterone (DHEA) concentration decreases with age. There is evidence that DHEA has a protective effect against age-related disorders, including cardiovascular disease. Accordingly, we examined the effect of DHEA supplementation (25 mg/d) on endothelial function, insulin sensitivity, and fibrinolytic activity in 24 men with hypercholesterolemia (mean age, 54 +/- 1 yr). All subjects were enrolled in a randomized, double-blind study. Flow-mediated dilation of brachial artery after transient occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
89
3
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 39 publications
9
89
3
3
Order By: Relevance
“…The selection of patients with low values of DHEA may have been an important factor for the finding of significant effects on body composition and fat distribution in that study, although other studies performed in men with low DHEA-S or women with adrenal insufficiency found no effects of DHEA on body composition (130,139). Finally, in the study by Kawano et al (127), although no effect on the lipid profile or body fatness were observed, other cardiovascular disease-related outcomes such as endothelial function and insulin sensitivity were significantly improved in response to DHEA supplementation in this sample of 24 hypercholesterolemic men, which may be considered as a cardioprotective effect of DHEA (127).…”
Section: Exogenous Dheamentioning
confidence: 49%
See 1 more Smart Citation
“…The selection of patients with low values of DHEA may have been an important factor for the finding of significant effects on body composition and fat distribution in that study, although other studies performed in men with low DHEA-S or women with adrenal insufficiency found no effects of DHEA on body composition (130,139). Finally, in the study by Kawano et al (127), although no effect on the lipid profile or body fatness were observed, other cardiovascular disease-related outcomes such as endothelial function and insulin sensitivity were significantly improved in response to DHEA supplementation in this sample of 24 hypercholesterolemic men, which may be considered as a cardioprotective effect of DHEA (127).…”
Section: Exogenous Dheamentioning
confidence: 49%
“…These studies were performed with dosage ranging from 25 to 1600 mg/day oral DHEA and durations from 4 to 36 weeks (127, 129 -131, 134 -137). Examining the effects of DHEA replacement in subjects with previously documented hypercholesterolemia did not lead to the finding of significant effects of the treatment in a 12-week randomized placebo-controlled study using 25 mg/day oral DHEA (127). On the other hand, some studies reported significant effects of DHEA on blood lipids (6, 11, 125,126,128,132,133).…”
Section: Exogenous Dheamentioning
confidence: 93%
“…Williams et al (12) showed a significant increase in FMD after the 12-week administration of DHEA (50 mg/day) in healthy postmenopausal women, while Silvestri et al (22) observed no effect using the same dose of DHEA for 4 weeks in postmenopausal women with increased cardiovascular risk. In middle-aged men, it has been reported that low-dose DHEA supplementation (25 mg/day) for 12 weeks improved FMD (23). Experimental studies have also demonstrated the effects of DHEA on endothelial proliferation (12) and endothelial nitric oxide synthase (24), further supporting the notion that DHEA(-S) has a protective effect on the endothelium.…”
Section: Discussionmentioning
confidence: 87%
“…These are also supported by our results in that the insulin sensitivity index HOMA-%S was inversely associated with serum ALT. DHEA is known to have potential to improve insulin sensitivity in vivo (21)(22)(23)(24). It also has properties to increase insulin sensitivity in hepatocytes (25).…”
Section: Discussionmentioning
confidence: 99%